Adoption and Integration of Modern Teaching Technologies in Higher Education: A Quantitative Study of Faculty Practices - Joshi, Prakash; Nyaupane, Netra Prasad (NPRC Journal of Multidisciplinary Research, 2024)
This is a quantitative study that represents the adoption and integration of modern teaching technologies by faculty members in higher education. Since technological tools are gaining much importance day by day in the improvement of learning outcomes, this research will help in filling up critical gaps in knowledge, attitude, and practices of faculties regarding these technologies. It was structured in a questionnaire type administered to all 46 faculties for data based on perceptions of and current use of modern teaching tools. Results show that conventional live classroom teaching is the primary mode of teaching at 60.90 percent, 17.40 percent utilize learning management systems, and only a few faculties use online collaborative tools at 6.50 percent. The attitude towards integrating technology is positive since 91.40 percent of male and 91.00 percent of female respondents acknowledged its contribution to learning. Still, this attitude differs across demographic groups and significantly in terms of age and teaching experience. While younger faculty are more likely to use modern technologies, older faculty rely more on traditional approaches. This study concludes that focused professional development and resource accessibility are the most influential factors that shape the improved technology integration in higher education.